Information literacy : recognising the need : Staffordshire University, Stoke-on-Trent, United Kingdom, 17 May 2006 - Walton, Geoff (Geoff L.); Pope, Alison (Chandos Pub., 2006)
This set of conference proceedings derives from the Information Literacy: Recognising the Need conference at Staffordshire University, 17 May 2006. The papers in this book discuss key themes in information literacy and have been written by several renowned experts in the field. Information literacy is not just about finding information: it is a true catalyst for educational change. It enables independent lifelong learning. These papers consider the position of information literacy in the higher education arena, how students bewitched by easy internet searching can be engaged in the learning process and how information professionals and academic colleagues might move in partnership towards the information literate university. Papers written by renowned experts in the field of information literacyHighlights a variety of topical issues - both practical and theoreticalGives a useful overview of information literacy for those previously unfamiliar with this aspect of teaching and learning.